2018
DOI: 10.1021/acsami.8b14526
|View full text |Cite
|
Sign up to set email alerts
|

On-Demand Dissolvable Self-Healing Hydrogel Based on Carboxymethyl Chitosan and Cellulose Nanocrystal for Deep Partial Thickness Burn Wound Healing

Abstract: Deep partial thickness burn wounds present big challenges due to the long healing time, large size and irregular shape, pain and reinjury at wound dressing changes, as well as scarring. The clinically effective therapy to alleviate pain at wound dressing changes, and the scar left on the skin after the healing of wound is still unavailable. To combat this, we develop a nanocomposite self-healing hydrogel that can be injected into irregular and deep burn wound beds and subsequently rapidly self-heal to reform i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
221
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(240 citation statements)
references
References 63 publications
2
221
0
Order By: Relevance
“…For example, after a wound is closed, it may need further handling, such as changing or adding medicines, according to the state of healing, which requires painlessly changing or removing the applied bioadhesives. [ 11,12 ] In addition, the closed wounds, especially those closed skin wounds, may be reopened during the post‐wound closure time, as shown by a clinical study which reported that about 26% of the groin skin wounds that were closed by bioadhesives were dehiscent and these reopened wounds require repeated closure to prevent the risk of infection and delayed healing. [ 13 ] Accordingly, developing a versatile bioadhesive that is capable of efficiently closing open wounds and enabling post‐wound closure care is imperative.…”
Section: Introductionmentioning
confidence: 99%
“…For example, after a wound is closed, it may need further handling, such as changing or adding medicines, according to the state of healing, which requires painlessly changing or removing the applied bioadhesives. [ 11,12 ] In addition, the closed wounds, especially those closed skin wounds, may be reopened during the post‐wound closure time, as shown by a clinical study which reported that about 26% of the groin skin wounds that were closed by bioadhesives were dehiscent and these reopened wounds require repeated closure to prevent the risk of infection and delayed healing. [ 13 ] Accordingly, developing a versatile bioadhesive that is capable of efficiently closing open wounds and enabling post‐wound closure care is imperative.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al described an injectable hydrogel prepared using carboxymethylchitosan and dialdehyde modified CNCs. 174 The gel demonstrated very good biocompatibility, self-healing and on-demand solubilisation under mildly acidic conditions. The gel was tested as a wound-healing agent in a deep partial thickness skin burn model in vivo and was shown to be effective for burn surface covering and treatment.…”
Section: Nc For Tissue Engineeringmentioning
confidence: 97%
“…In view of this issue, Zhang and coworkers developed self‐healing hydrogel nanocomposites, which were made of carboxymethyl chitosan and cellulose nanocrystals. It can be injected into burn wounds to fully cover the wound sites, followed by rapidly transferring into an integrated hydrogel that thoroughly filled the wound region and isolated the wound site from external environment, and finally painlessly removed by dissolving with amino acid solution . Besides, Zhao and coworkers proposed a hybrid hydrogel consisted of a benzaldehyde‐terminated polyethylene glycol and dodecyl‐modified chitosan.…”
Section: Biomedical Applications Of Polysaccharides and Polysaccharidmentioning
confidence: 99%